1995
DOI: 10.2351/1.4745372
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy

Abstract: Photodynamic therapy (PDT) is a new treatment for solid tumors utilizing the combined action of light and a photosensitizing drug. Laser-fiber optic delivery systems make it practical to treat superficial and interstitial cancers, including malignancies of the skin, head and neck, esophagus, endobronchial tract, stomach, urinary bladder, female genital tract, and other sites. The putative action mechanism in PDT involves photochemical destruction of tumor tissue membranes mediated by singlet molecular oxygen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Tumor cells have higher numbers of LDL receptors on their surfaces, potentially associated with their higher requirement for cholesterol than normal cells to build membranes 47 . Several studies have achieved preferential photosensitizer release to tumor cells by associating the photosensitizers with low density lipoproteins and by increasing hydrophobicity by augmentation with liposome delivery systems 48–50 . However, other reports have shown that a degree of selectivity does not correlate with their hydrophobicity or their affinity for LDL, indicating that LDL receptor‐mediated pathway may not be the main route of internalization 15,51 …”
Section: Photosensitizer Localization In Neoplastic Tissuementioning
confidence: 99%
“…Tumor cells have higher numbers of LDL receptors on their surfaces, potentially associated with their higher requirement for cholesterol than normal cells to build membranes 47 . Several studies have achieved preferential photosensitizer release to tumor cells by associating the photosensitizers with low density lipoproteins and by increasing hydrophobicity by augmentation with liposome delivery systems 48–50 . However, other reports have shown that a degree of selectivity does not correlate with their hydrophobicity or their affinity for LDL, indicating that LDL receptor‐mediated pathway may not be the main route of internalization 15,51 …”
Section: Photosensitizer Localization In Neoplastic Tissuementioning
confidence: 99%
“…Apoptotic cells were recognized by their smaller size and nuclei fragmented into condensed chromatin bodies. The results were validated against a standard induction of apoptosis by heat treatment at 43°C for 40 min followed by incubation for 4 h at 37°C according to the method described by Li et al (1994). One hundred cells in four preparations (total of 400 cells) were counted by two individuals, independently.…”
Section: Determination Of Percentage Of Apoptotic Cellsmentioning
confidence: 99%
“…The leading, most widely investigated, photosensitizers in PDT are the haematoporphyrins (HPDPhotofrin II) (Kessel, 1984), which were recently approved for clinical use. However, their use may be limited because of prolonged cutaneous phototoxicity, aggregation tendency, slow metabolism in vivo (Gomer, 1991;Grossweiner, 1994;Jones et al, 1996), as well as limited efficacies in affecting penetrating solid tumours (Orenstein et al, 1996). To overcome these limitations, a number of photosensitizing molecules are being investigated as potential agents for use in PDT.…”
mentioning
confidence: 99%
“…PDT has been receiving increasing attention as an important approach for cancer treatment [45,75]. Many compounds can be used as photosensitizers in PDT with low systemic toxicity and excellent biocompatibility [76,77].…”
Section: Photosynthesis-boosted Photodynamic Therapymentioning
confidence: 99%
“…A few cancer therapies, for example, radiotherapy (RT) and photodynamic therapy (PDT), also require oxygen to enhance efficacy [42][43][44]. PDT employs a light-activated photosensitizer to deliver energy to oxygen and then generates highly reactive singlet oxygen, which destroys tumor tissue by inducing cellular necrosis, apoptosis, acute inflammation, and attraction of leukocytes to the targeted tumors [45][46][47]. There are some oxygen-replenishing strategies for such therapies, including catalyzing endogenous H 2 O 2 with organic or inorganic catalysts [48][49][50], water splitting [51][52][53], oxygen transport [54,55], and respiratory inhibitors [56].…”
Section: Introductionmentioning
confidence: 99%